Promoting Sales of Energy Efficient Household Appliances: Outcomes and Cost Effectiveness of Rebate Programs - Thiess Büttner; Boryana Madzharova (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper studies seven rebate programs aiming at accelerating the replacement of energy-intensive household appliances. Based on a large product-level data set for several European countries, we study the effects on unit sales and prices of both subsidized and non-subsidized products. The empirical identification strategy exploits the temporary implementation of the rebates in regional segments of the European Common Market. The results for unit sales indicate that subsidies can be an effective instrument for stimulating purchases of energy efficient appliances. While the strength of the stimulus proves sensitive to program design, we find limited evidence of intertemporal substitution, and no indication that program effects are driven by a drop in sales of non-subsidized products. In some cases, sales of non-subsidized products increase, a finding that we attribute to information campaigns associated with the rebate programs. Price effects are modest, implying that subsidies are mostly passed through to consumers. Considering the actual energy savings, however, our analysis shows that rebate programs are a relatively expensive way to improve energy efficiency.
Keywords: H23; Q48; D12; 330; rebate programs; energy efficiency; household appliances; program evaluation